2018
DOI: 10.1002/sce.21459
|View full text |Cite
|
Sign up to set email alerts
|

Identity negotiation within peer groups during an informal engineering education program: The central role of leadership‐oriented youth

Abstract: As part of ongoing efforts to support a diverse and robust engineering workforce and ensure that children and adults from all communities have the engineering and design thinking skills to succeed in a science, technology, engineering, and mathematics (STEM)‐rich world, identity has become a growing focus of research and education efforts. To advance our understanding of engineering‐related identity negotiation within informal STEM education contexts, we conducted an in‐depth, qualitative investigation of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…First, social networks in support of learning and doing engineering can be expanded by involving community members—not just peers and STEM experts—in engineering design. Pattison, Gontan, Ramos‐Montañez, and Moreno () in their work on recognizing and positioning the situated identities of youth in engineering design activities state: “Youth, and especially those from traditionally underserved and underresourced communities, often must juggle multiple identities and navigate a variety of social and cultural barriers as they develop their relationships with engineering and STEM” (p. 1001). In Christopher's positionality statement, although he was recognized by his Green Club peers, David and Kaleel and his STEM mentors, he still did not feel that his engineering work was transformative for the people that would be best benefitted by his engineering design.…”
Section: Discussionmentioning
confidence: 99%
“…First, social networks in support of learning and doing engineering can be expanded by involving community members—not just peers and STEM experts—in engineering design. Pattison, Gontan, Ramos‐Montañez, and Moreno () in their work on recognizing and positioning the situated identities of youth in engineering design activities state: “Youth, and especially those from traditionally underserved and underresourced communities, often must juggle multiple identities and navigate a variety of social and cultural barriers as they develop their relationships with engineering and STEM” (p. 1001). In Christopher's positionality statement, although he was recognized by his Green Club peers, David and Kaleel and his STEM mentors, he still did not feel that his engineering work was transformative for the people that would be best benefitted by his engineering design.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more collaborative approaches have been found to help retain girls in male-dominated subjects, such as computer science, engineering, and physics (Weisul, 2017). There exists a large body of research that shows collaboration can be used to engage a more diverse population in engineering and to help individuals construct engineering identities (Busch-Vishniac & Jarosz, 2004;Cunningham & Lachapelle, 2014;Goodman et al, 2002;Menekse et al, 2017;Pattison et al, 2018). Teamwork provides students with opportunities to contribute in a variety of ways, thereby placing value on diversity rather than creating hierarchies with competition.…”
Section: Collaborationmentioning
confidence: 99%
“…Our analysis is based on a situated perspective of identity (Gee, 2000), which considers how identities are context-dependent and negotiated with oneself and between oneself and others. In line with research on measures of situated science and engineering identity, in this study we defined engineering identity as consisting of two dimensions: thinking of oneself as an engineer and being thought of by others as an engineer (Calabrese Pattison et al, 2018;Tonso, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They offer hands‐on experience, develop students' social and motor skills, and foster student motivation to learn (Itzek‐Greulich et al, ; Lavie Alon & Tal, ). Informal environments can play a key role in the development of scientific literacy, skills, dispositions, practices, and knowledge (Mujtaba, Lawrence, Oliver, & Reiss, ; Peleg & Baram‐Tsabari, ; Wünschmann, Wüst‐Ackermann, Randler, Vollmer, & Itzek‐Greulich, ), as well as science identity (Pattison, Gontan, Ramos‐Montañez, & Moreno, ; Williams et al, ).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Similarly, Goff, Mulvey, Irvin, and Hartstone‐Rose () found that young people who reported participation in informal programs prior to college also reported higher academic aspirations and greater interest and engagement with STEM (see also Dou, Hazari, Dabney, Sonnert, & Sadler, ). Supporting the development of science identities has the potential to afford equal access to science (Pattison et al, ; Williams et al, ).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%